Cytoplasmic injection of circular plasmids allows targeted expression in mammalian embryos. (November 2009) - Iqbal, Khursheed; Barg-Kues, Brigitte; Broll, Sandra; Bode, Jürgen; Niemann, Heiner; Kues, Wilfried A.
Injection of linearized DNA constructs into the pronuclei of fertilized mammalian eggs is a standard method for producing transgenic embryos and animals. Here, we show that injection of covalently closed circular (ccc) plasmids into the cytoplasm of fertilized bovine and murine eggs is a highly efficient and simple alternative for ectopic expression of foreign DNA in embryos. A broad range of plasmids could be successfully expressed in preimplantation stages, including plasmids and minicircles with a scaffold/matrix attachment region (S/MAR), conventional plasmids, and bacterial artificial chromosomes (BACs). Although the foreign DNA plasmids are mainly maintained as episomal entities during preimplantation development, they accurately behave like nuclear DNA. Onset of transcription of an Oct4 promoter–controlled marker gene coincided with the species-specific time points of major embryonic genome activation, and could be modulated by in vitro DNA-methylation. This approach allows an experimental access to reprogramming events in early mammalian embryos.